2019
DOI: 10.1051/0004-6361/201834146
|View full text |Cite
|
Sign up to set email alerts
|

Binarity among CEMP-no stars: an indication of multiple formation pathways?

Abstract: Carbon-enhanced metal-poor (CEMP) stars comprise a large percentage of stars at the lowest metallicities. The stars in the CEMP-no subcategory do not show any s-process enhancement and therefore cannot easily be explained by transfer of carbon and s-process elements from a binary AGB companion. We have performed radial velocity monitoring of a sample of 22 CEMP-no stars to further study the role binarity plays in this type of CEMP star. We find four new binary CEMP-no stars based on their radial velocity varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 100 publications
7
56
0
Order By: Relevance
“…Their estimated binary periods fall in the same range as CEMP-s stars, which is consistent with the expectation that the Group II and Group III stars belong to long period binaries. Indeed, one of the Group III stars, HE 0107-5240, was reported to have a companion star whose binary period is longer than 10000 days (Arentsen et al 2019). We also note that some CEMP-no stars also show Eu/Ba ratio predicted by the s-process nucleosynthesis, and that the distribution of [Ba/Fe] of CEMP-no stars is different from that of C-normal EMP stars (Yamada et al 2019b).…”
Section: Introductionmentioning
confidence: 52%
“…Their estimated binary periods fall in the same range as CEMP-s stars, which is consistent with the expectation that the Group II and Group III stars belong to long period binaries. Indeed, one of the Group III stars, HE 0107-5240, was reported to have a companion star whose binary period is longer than 10000 days (Arentsen et al 2019). We also note that some CEMP-no stars also show Eu/Ba ratio predicted by the s-process nucleosynthesis, and that the distribution of [Ba/Fe] of CEMP-no stars is different from that of C-normal EMP stars (Yamada et al 2019b).…”
Section: Introductionmentioning
confidence: 52%
“…In spite of the large errors on their four measurements, the indication was clear that the radial velocity of HE 0107−5240 was almost 4 km s −1 larger than it was in the time interval 2001-2006. On this basis, Arentsen et al (2019) suggested that the scenario of mass transfer in this star becomes highly likely. We note that mass transfer can also occur in a very wide binary, if it happens mainly through the stellar wind (Abate et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the meanwhile, Arentsen et al (2019) presented some low quality radial velocity measurements obtained with the High Resolution Spectrograph (Bramall et al 2012) on the Southern African Large Telescope (SALT; Buckley et al 2006). In spite of the large errors on their four measurements, the indication was clear that the radial velocity of HE 0107−5240 was almost 4 km s −1 larger than it was in the time interval 2001-2006.…”
Section: Introductionmentioning
confidence: 99%
“…Caffau et al 2016), but their abundances reflect the chemistry of the gas cloud in which they formed. Recently, Arentsen et al (2019) found four binary systems in a sample of CEMP-no stars, but the fact that some of these stars are binaries is not unexpected.…”
Section: A46 Page 1 Of 10mentioning
confidence: 98%